Experimental Research on Fire Resistance of Reactive Powder Concrete - Gai-Fei Peng; Yi-Rong Kang; Yan-Zhu Huang; Xiao-Ping Liu; Qiang Chen (Advances in Materials Science and Engineering)
An experimental investigation was conducted on fire resistance of reactive powder concrete (RPC), mainly on explosive spalling occurrence and residual mechanical properties exposed to high temperature. The residual mechanical properties measured include compressive strength, tensile splitting strength, and fracture energy. RPC was prepared using cement, sand, silica fume, steel fiber, and polypropylene fiber. After subjected to high temperatures from 200 to 600°C, the residual mechanical properties were determined. RPC spalled considerably under high temperature. After exposure to high temperatures from 200 to 400°C, mechanical properties were enhanced more or less, which can be attributed to further hydration of cementitious materials activated by elevated temperature. Compressive strength started to decrease after exposure to 400°C, but tensile splitting strength and fracture energy started to decrease after exposure to 200°C. Incorporating hybrid fiber (polypropylene fiber and steel fiber) is a promising way to enhance resistance of RPC to explosive spalling, which should be a main objective for improving its fire resistance.